Endocrine and multiple sclerosis outcomes in patients with autoimmune thyroid events in the alemtuzumab CARE-MS studies - Dayan, Colin M; Lecumberri, Beatriz; Muller, Ilaria; Ganesananthan, Sashiananthan; Hunter, Samuel F; Selmaj, Krzysztof W; Hartung, Hans-Peter; Havrdova, Eva K; LaGanke, Christopher C; Ziemssen, Tjalf; Van Wijmeersch, Bart; Meuth, Sven G; et al. (Multiple sclerosis journal - experimental, translational and clinical, 2023)
BACKGROUND: Alemtuzumab is an effective therapy for relapsing multiple sclerosis. Autoimmune thyroid events are a common adverse event. OBJECTIVE: Describe endocrine and multiple sclerosis outcomes over 6 years for alemtuzumab-treated relapsing multiple sclerosis patients in the phase 3 CARE-MS I, II, and extension studies who experienced adverse thyroid events. METHODS: Endocrine and multiple sclerosis outcomes were evaluated over 6 years. Thyroid event cases, excluding those pre-existing or occurring after Year 6, were adjudicated retrospectively by expert endocrinologists independently of the sponsor and investigators. RESULTS: Thyroid events were reported for 378/811 (46.6%) alemtuzumab-treated patients. Following adjudication, endocrinologists reached consensus on 286 cases (75.7%). Of these, 39.5% were adjudicated to Graves' disease, 2.5% Hashimoto's disease switching to hyperthyroidism, 15.4% Hashimoto's disease, 4.9% Graves' disease switching to hypothyroidism, 10.1% transient thyroiditis, and 27.6% with uncertain diagnosis; inclusion of anti-thyroid antibody status reduced the number of uncertain diagnoses. Multiple sclerosis outcomes of those with and without thyroid events were similar. CONCLUSION: Adjudicated thyroid events occurring over 6 years for alemtuzumab-treated relapsing multiple sclerosis patients were primarily autoimmune. Thyroid events were considered manageable and did not affect disease course. Thyroid autoimmunity is a common but manageable adverse event in alemtuzumab-treated relapsing multiple sclerosis patients.ClinicalTrials.gov Registration Numbers: CARE-MS I (NCT00530348); CARE-MS II (NCT00548405); CARE-MS Extension (NCT00930553).
Keywords: Alemtuzumab; multiple sclerosis; thyroid; Hashimoto's disease; disease-modifying therapy; Graves’ disease